NATION BUILDING THROUGH THE PATHWAY OF EDUCATION: A POLICY REFLECTION WITHIN THE ROADMAP OF NATIONAL DEVELOPMENT - Wildan Miftahussurur; Su’udin Aziz; Akhmadi Akhmadi (FORPIM PTKIS ZONA TAPAL KUDA, 2025)
Education plays a pivotal role in shaping a nation's civilization that is both competitiveand sustainable. This article aims to examine how educational policy functions as afundamental pillar in the development of the Indonesian nation. Employing aqualitative methodology, the study focuses on government regulations, nationaldevelopment planning documents (RPJMN), and academic literature on educationalpolicy and national development. The findings reveal that social transformation,enhanced global competitiveness, and the improvement of human capital quality canbe achieved through educational policies that align with the national developmentvision. Education is not merely a public service; it is a long-term investment withprofound structural implications for a nation’s progress. Therefore, it is imperativethat educational policy be synergized with other strategic sectors such as technology,the economy, and public health. The study concludes that educational policies must beintegrative, rooted in national values, and responsive to emerging global challenges.